Thieme Chemistry Journals Awardees: Where Are They Now? One-Pot Synthesis of Versatile Buckle Units for Click Chemistry: 4,8-Diazacyclononynes (DACNs) - Igawa, Kazunobu; Aoyama, Shin; Kawasaki, Yuuya; Kashiwagi, Takeru; Seto, Yuki; Ni, Runyan; Mitsuda, Naoto; Tomooka, Katsuhiko (Synlett, 2017)
Newly designed buckle units for copper-free click chemistry: 4,8-diazacyclononynes (DACNs) were efficiently synthesized with a one-pot procedure from commercially available 2-butyne-1,4-diol. The synthesized DACNs possess versatile connectors for the introduction of functional units and exhibit high click reactivity.
Keywords: click chemistry; Huisgen reaction; strained alkyne; Nicholas reaction; one-pot synthesis